Incidence of Pneumonia in Sheep in El-Jabal El-Akhdar (Libya) - Mahmoud, Ghyath Salih; Mohammed, Moneer El-Saber (Al-Mukhtar Journal of Sciences, 2008)
This study involved certain investigations on pneumonic lesions in sheep in Al-Jabal Al-Akhdar district .Therefore 630 lungs of sheep were examined periodically in Shahat, Quba and Al-Bieda slaughter houses during the year 2003-2005 .However (62) lungs were found to be affected and showed various pneumonic lesions which resembled about 9.8% from the total lungs examined . These pneumonic lungs were classified into verminous pneumonia (3.1%), bacterial pneumonia (2.8%), viral pneumonia (0.8%), Mycotic pneumonia (0.8%) and interstitial pneumonia (2.3%) .Moreover the gross and microscopic details for these pneumonic lungs were included in this study .